THE CORRELATION BETWEEN LEARNING MOTIVATION AND PARENT ECONOMIC LOW CONDITION TOWARD STUDENTS ENGLISH ACHIVEMENT AT EIGHT GRADE OF MTs ALKHAIRAT GINUNGGUNG - Sata, Moh. Rafi’i Moh. (Universitas Madako Tolitoli, 2021)
The purpose of this study was to know is there any correlation between learning motivation and parents economic low condition toward students english achievement. This research is a correlation study. Data obtained from questionnaires, interviews and documentation. Data collection techniques in this study using random sampling. In measuring correlation, researcher used the SPSS 21 program. The results of this research indicates that the known that the learning motivation of students english achivementÂ is 0.188> 0.05. It shows that there is no correlation between learning motivation and students' English achivement. Second, parents economic low condition toward students english achivement is 0.29> 0.05. This shows that there is no correlation between parents economic low condition towards students english achievement. The final result, learning motivation and parents economic low condition toward students english achivement is similely 0.831> 0.05. So it can be concluded that there is no correlation between learning motivation and parents economic low condition toward students english achivement in class VIII MTs Alkhairat Ginunggung.